Substituted naphthoxy-phthalonitrile derivatives: Synthesis, substituent effects, DFT, TD-DFT Calculations, antimicrobial properties and DNA interaction studies. (February 2023) - Erdoğan, Musa; Başkan, Ceren; Serdaroğlu, Goncagül
Abstract: Herein, substituted-naphthol derivatives 4a–e were synthesized in two steps, namely the Diels Alder cycloaddition and Cu-catalyzed aromatization reactions, respectively. Then, pththalonitrile derivatives 7–12 have been prepared by a nucleophilic displacement reaction of 3-nitrophthalonitrile with the naphthol derivatives 4a-e, 5 and, obtained in excellent yields. Structural characterization of the compounds was identified by different spectroscopic techniques. Antimicrobial properties of the synthesized compounds were determined by the microdilution procedure against Gram-positive, Gram-negative bacteria, and yeast. Furthermore, the DNA interaction of the compounds were determined by gel electrophoresis. One of the most prominent findings is that compounds 9 and 10 have more inhibitory effects on Gram-positive bacteria than Gram-negative bacteria. These compounds especially exhibited the highest antibacterial potency against S. aureus (625 µg/mL) among Gram-positive bacteria. According to the plasmid DNA interaction results, the synthesized compounds caused changes in the structure and mobility of the plasmid DNA. Then, geometry optimizations and frequency calculations were conducted at B3LYP/6–311 G(d, p) level of DFT, and optimized structures were used for further analyses. The NBO results revealed that the π→π * and n→π * interactions were greatly contributed to lowering the stabilization energy of all compounds (7–12 ). FMO energy analyses showed that compound 9 has the biggest electrodonating power. Graphical Abstract: ga1 Highlights: Six different phthalonitrile derivatives were designed and synthesized. The phthalonitrile derivatives were fully characterized. DFT and TD-DFT computations were performed. FMO and NBO analyses were conducted. Antimicrobial activities and plasmid DNA interactions were screened.